How to solve Fokker-Planck equation treating mixed eigenvalue spectrum? - Brics, M.; Kaupuzs, J.; Mahnke, R. (Condensed Matter Physics, 2013)
An analogy of the Fokker-Planck equation (FPE) with the Schrödinger equation allows us to use quantum mechanics technique to find the analytical solution of the FPE in a number of cases. However, previous studies have been limited to the Schrodinger potential with discrete eigenvalue spectrum. Here we will show how this approach can be applied also for mixed eigenvalue spectrum with bounded and free states. We solve the FPE with boundaries located at x=±L/2 and take the limit L→∞, considering examples with constant Schrödinger potential and with Pöschl-Teller potential. An oversimplified approach has been earlier proposed by M.T. Araujo and E. Drigo Filho. A detailed investigation of the two examples shows that the correct solution, obtained in this paper, is consistent with the expected Fokker-Planck dynamics. Аналогiя рiвняння Фоккера-Планка (FPE) з рiвнянням Шредингера дозволяє використати метод квантової механiки для знаходження аналiтичного розв’язку FPE для низки випадкiв. Проте, попереднi дослiдження обмежувалися потенцiалом Шредингера з дискретним спектром власних значень. Тут ми покажемо, як цей пiдхiд можна також застосувати до спектру змiшаних власних значень зi зв’язаними i вiльними станами. Ми розв’язуємо FPE з границями, що знаходяться при x = ±L/2 i беремо границю L → ∞, розглядаючи приклади з постiйним потенцiалом Шредингера i потанцiалом Пешля-Теллера. Спрощений пiдхiд ранiше запропонували M.T. Араухо та E. Дрiго Фiльйо. Детальне дослiдження двох прикладiв показує, що коректний розв’язок, отриманий в цiй статтi, узгоджується з очiкуваною динамiкою Фоккера-Планка.